Nevus Unius Lateris (NUL) in a Theree-Year-Old Child Treated by Tretinoin 0.025%, Desoxymethasone 0.25%, and Urea 20% Cream - Stephanie, Aurelia; Vibriyanti Karna, NLP Ratih; Karmila, IGAA Dwi; Laksmi, Hermina; Stella, Aurelia (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Linear verrucous epidermal nevus is the most frequent variant of the epidermal nevus classification. Linear verrucous epidermal nevus is characterized by the proliferation of epithelium arranged in a configuration that follows Blaschko's line. Nevus unius lateris (NUL) is a variant of the verrucous epidermal nevus, which has a unilateral distribution of lesions. Lesions are usually found at birth or in the first year of life as brown to grey verrucous papules or papillomatous plaques. The management of NUL is challenging as the results are varied and there is a high risk of recurrence. Purpose: to report a case of NUL and its management, especially in children. Case: A 3-year-old girl presented with brownish spots and multiple small lumps on the left buttock that have extended to the left leg since she was 9-days-old. On dermatologic examination, there were numerous hyperpigmented verrucous papules and plaques along the Blaschko line over the affected area. In this case, the diagnosis of NUL, is based on clinical symptoms and dermoscopy examination showed multiple large brown oval or round structures with hyperpigmented brown border. The patient was treated with combination topical therapy of tretinoin 0.025%, corticosteroid desoxymethasone 0.25%, and urea 20% cream, and the lesion improved within four weeks. Discussion: Epidermal nevus is often cosmetically disturbing. The treatment is still challenging and various, including surgical and non-surgical, but none is ideal and could potentially recur over months or years. dst.